Performance of transgenic Bt cotton of different Bt events under IPM in rainfed situation - PATIL, S B; BADIGER, HAREESHA K; BHOSLE, B B (The Indian Journal of Agricultural Sciences, 2014)
The field experiment was carried out at ARS, Dharwad farm, Karnataka, India during 2010-11 to study the performance of Bt cotton hybrids, viz. Bunny BG-I, Bunny BG-II, JK Durga and Nathbaba developed through different Bt events under IPM practices. The performance of the Bt hybrids with IPM practices (module) was compared with farmers practices. IPM module encompassed, Bt cotton seeds treated with imidacloprid 70WS, sowing of redgram as a refuge, detopping of shoot tip, installation of pheromone traps, and selective use of chemicals for sucking pests control, whereas farmers practice relied only on chemical interventions. The results revealed that among the Bt genotypes, Bunny BG-II under IPM, recorded lower population of aphids, thrips, leaf hopper and mirid bugs (3.94,9.09,2.07/3 leaves and 3.10/25 squares respectively) followed by Bunny BG-I(4.44, 9.74, 2.26/3 leaves and 3.12/25 squares respectively). However non-significant variation among the genotypes was observed under IPM. Further, irrespective of the modules, bollworm population was not observed in any of the Bt cotton genotypes. Although the larval population of Helicoverpa was recorded in Non Bt, the population was considerably low with IPM practice (0.98/plant) as compared to the farmers practice (1.96/plant) due to target specific interventions. The fruiting bodies damage was negligible in both the modules with hybrids containing two genes compared to hybrids with single Bt gene. On the contrary, modules with non Bt cotton registered significantly higher fruiting bodies damage. Among the genotypes, Bunny BG-II integrated in IPM registered higher seed cotton yield of 25.20 q/ha followed by 24.57 q/ha in Nathbaba with more profit. It is evident from the results that performance of Bunny BG-II was found to be better as indicated by lower infestation and higher seed cotton yield under IPM practice.